KONVERSI LAHAN PERTANIAN PADA KORIDOR JALAN SOLO-YOGYAKARTA DI KABUPATEN KLATEN - Sri Rahayu; Iwan Rudiarto; Pangi Pangi (Department of Urban and Regional Planning, Diponegoro University, 2015)
This research aims to assess the conversion of agricultural land in the Solo-Yogyakarta corridor of Klaten Regency (Kabupaten) during 1994-2013. It is important because the Solo-Yogyakarta arterial road in Kabupaten Klaten affects the land use of the surrounding area. This research has used spatial analysis methods, i.e. interpreting the Landsat and ALOS satellite imageries, overlaying land use maps, and comparing the land use map and the spatial plan map (RTRW) of Kabupaten Klaten. The results show that conversion of agricultural land during the period of 1994-2013 was 424.82 ha, most of which was converted into residential and industrial use. So, the average loss of agricultural land has been about 22.35 ha/year while residential land has increased by 19.84 ha/year. The largest conversion happened in the Banaran Village. Meanwhile, land use that was not in accordance with the RTRW was 69.15 ha (0.90 %). © 2015 GJGP UNDIP. All rights reserved.